Nurfa Bakery & Cake House / Nur Nadia Azmi - Azmi, Nur Nadia (2020)
Nurfa Bakery & Cake House is a business that base on cake, bread and cookies. It is where the product has been made fresh from oven. They provide many various types of cake, bread and cookies. The location of the premise is a strategic location in Melor town. This business is actually a family business and now these bakeries was given to the new owner to rebranding and make a new one followed to era 2020. She renews some menu on the bakery and has a special menu that makes her customer always want to have it. The entrepreneurial characteristic of Nurfa have are sees that she can improve her business.